Knowledge of health workers on snakes and snakebite management and treatment seeking behavior of snakebite victims in Bhutan. - Sunil Sapkota; Deb P Pandey; Guru P Dhakal; Dhan B Gurung (Public Library of Science (PLoS), 2020)
Background Published information on snakebite is rare in Bhutan although remarkably higher number of snakebites and associated deaths are reported from other South Asian countries. Aims and methodology Structured questionnaire was used to collect knowledge of health workers in snakebite management and health seeking behavior of snakebite victims as observed by health workers. Study was conducted in purposively sampled 10 Dzongkhags (district level administrative units) with higher incidence of snakebites. Result Heath workers scored 27-91% (with an average of 63%, SD = 14) for 52 questions related to snake identification and snakebite management. Among 118 health workers interviewed, 23% had adequate knowledge on snakes and snakebite management while 77% had inadequate knowledge. Among 32 Doctors, 63% of them scored above or equal to 75%. Health workers from Sarpang scored higher (76%, SD = 11) than those from other Dzongkhags. Snakebite victim's visit to local (traditional) healers prior to seeking medical help from hospital was observed by 75 (63%) health workers. Fifty one percent of health workers observed patients treated with local methods such as the use of black stone called Jhhar Mauro (believed to absorb snake venom), application of honey, rubbing of green herbal paste made up of Khenpa Shing (Artemisia myriantha Wallich ex Besser var. paleocephala [Pamp] Ling) and consumption of fluid made up of Neem leaf (Azadirachta indica Juss). Use of tight tourniquet as a first aid to snakebite was observed by 80% of the health workers. Conclusion Health workers lack confidence in snakebite management. Snakebite victims are likely to suffer from harmful local practices and traditional beliefs on local treatment practices. Empowering health workers with adequate knowledge on snakebite management and making locals aware in pre-hospital care of snakebites are needed to improve the pre- and in-hospital management of snakebite in Bhutan.